Pulmonary Tuberculosis Patients and Management in Dentistry at Puskesmas Palmerah - Theresia, Tiarma Talenta; Lestari, Sri; Hibatillah, Ahmad Dzaki; Widyanto, Petronella; Tobing, Fiona Priscilia Dinata; Maringka, Stella Maria Fidela; Syaqila, Abigail Rifda; Annisa, Fauziah Rahma; Amanda, Nabila Risqy; Jordan, Bryan Matthew (Universitas Ibn Khaldun Bogor, 2025)
Background: Palmerah Health Center, located in Palmerah Subdistrict, West Jakarta, with a population of 233,917 people in 2022, faces challenges in dealing with infectious diseases like Tuberculosis (TB). Pulmonary TB, caused by Mycobacterium tuberculosis, primarily affects the lungs but can spread to other organs. Common symptoms of pulmonary TB include coughing with sputum for more than two weeks and shortness of breath. Objective: To understand the overview of pulmonary tuberculosis in the Palmerah area and the risk factors contributing to TB in the Palmerah region. Methodology: This study is an observational descriptive research with a cross-sectional design, using data from the online-based Tuberculosis Information System (SITB) at Palmerah Health Center and all its supporting health centers (Pustu) in Palmerah Subdistrict. Results: The highest number of pulmonary tuberculosis cases was found at Palmerah Health Center, followed by Palmerah Village Health Center. Pulmonary tuberculosis cases were more common in males. Conclusion: Pulmonary tuberculosis cases in Palmerah remain relatively high, with complex contributing factors. The TB case screening program conducted by the health centers shows good cross-sectoral support, but there are still barriers related to human resources and the community's knowledge and understanding of TB prevention.